2016
DOI: 10.1523/jneurosci.0628-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Activation of  -Glucocerebrosidase Reduces Pathological  -Synuclein and Restores Lysosomal Function in Parkinson's Patient Midbrain Neurons

Abstract: Parkinson's disease (PD) is characterized by the accumulation of ␣-synuclein (␣-syn) within Lewy body inclusions in the nervous system. There are currently no disease-modifying therapies capable of reducing ␣-syn inclusions in PD. Recent data has indicated that loss-offunction mutations in the GBA1 gene that encodes lysosomal ␤-glucocerebrosidase (GCase) represent an important risk factor for PD, and can lead to ␣-syn accumulation. Here we use a small-molecule modulator of GCase to determine whether GCase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
191
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(204 citation statements)
references
References 46 publications
(24 reference statements)
5
191
0
Order By: Relevance
“…Interestingly, miR-7 played a role in insulin secretion by repressing the expression of α-synuclein which in turn modulated the granule fusion with the plasma membrane. These results are in line with the previous observation that α-synuclein, whose exact function still remains unknown, plays a role in neurotransmitter release via regulating the pool of vesicles available in the synaptic bouton and its fusion with the plasma membrane (Murphy et al, 2000; Cabin et al, 2002; Fernández-Chacón et al, 2004; Chandra et al, 2005; Larsen et al, 2006; Mazzulli et al, 2016). …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, miR-7 played a role in insulin secretion by repressing the expression of α-synuclein which in turn modulated the granule fusion with the plasma membrane. These results are in line with the previous observation that α-synuclein, whose exact function still remains unknown, plays a role in neurotransmitter release via regulating the pool of vesicles available in the synaptic bouton and its fusion with the plasma membrane (Murphy et al, 2000; Cabin et al, 2002; Fernández-Chacón et al, 2004; Chandra et al, 2005; Larsen et al, 2006; Mazzulli et al, 2016). …”
Section: Resultssupporting
confidence: 89%
“…Supporting evidence includes: (i) duplications and triplication of the α-synuclein gene cause dominantly inherited PD, with a dose-correlation of α-synuclein load to the PD phenotype (Singleton et al, 2003; Ibáñez et al, 2004, 2009; Ahn et al, 2008; Ross et al, 2008); (ii) polymorphisms in α-synuclein promoters are associated with increased PD risk by enhancing α-synuclein expression (Chiba-Falek and Nussbaum, 2001; Touchman et al, 2001; Maraganore et al, 2006); (iii) increased α-synuclein mRNA levels are found in surviving dopaminergic (DA) neurons in the substantia nigra (SN) of idiopathic PD patients (Gründemann et al, 2008); (iv) induced pluripotent stem cells (iPS) from PD patients exhibited α-synuclein accumulation (Nguyen et al, 2011; Sánchez-Danés et al, 2012; Mazzulli et al, 2016); (v) α-synuclein is up-regulated in several in vivo PD models including 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mice and monkeys (Vila et al, 2000, 2001; Purisai et al, 2005); and (vi) overexpression of human wild-type and A53T mutant α-synuclein in rats and monkeys induced nigrostriatal degeneration (Kirik et al, 2002, 2003). In addition to PD, α-synuclein plays a key role in and other synucleinopathies such as dementia with Lewy bodies (DLB) and multiple system atrophy (MSA; Tagliafierro and Chiba-Falek, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dopaminergic neurons from idiopathic PD patients (iPD1, (11); iPD2, fig. S1, E and F) also manifested a similar phenotype, including decreased basal respiration and oxidized dopamine accumulation, but at later time points (d150, d180) (Fig.…”
Section: Neuromelanin and Oxidized Dopamine Accumulate In Dopaminergimentioning
confidence: 99%
“…In contrast, some reports indicate that the C-terminal acidic tail is indeed necessary but not sufficient for the chaperone function of α-Syn [28,29]. In normal physiological conditions, α-Syn exists in monomeric form and is recognized and cleared via the ubiquitin-proteasome system (UPS) and chaperone-mediated autophagy (CMA) pathways [39] (Figure 2). In the pathological state, misfolding or mutations of α-Syn (A30P/A53T) lead to the formation of pathologically modified species that bind with several cytoplasmic proteins and ultimately aggregate into LBs in the DA neuronal cells [40] ( Figure 2).…”
Section: α-Syn Structure and Functionmentioning
confidence: 99%